Early-life adversity and edentulism among Chinese older adults - Ziqing Tang; Chuanlong Huang; Yang Li; Ying Sun; Xin Chen (BMC, 2022)
Abstract Background Emerging evidence indicate the relationship between ELA with oral health problems. However, most focus on single types of adversity. The association of cumulative ELA with edentulism, the final marker of disease burden for oral health, remains unclear. Methods Data came from 17,610 elderly participants in the China Health and Retirement Longitudinal Study (CHARLS). In 2014, the Life History Survey Questionnaire was utilized to evaluate the experience of threat and deprivation. Information on edentulism was evaluated through self-report from the follow-up in 2013, 2015, and 2018. By controlling for age, education, hukou residence, marital status, and disease history, logistic regression analyses were used to evaluate the relationships between distinct dimensions of ELA and risk of edentulism. Results Nearly half (49.8%) of the 17,610 older persons (mean [SD] age at baseline: 63.6 [9.4] years) reported experiencing early adversity due to threat-related ELA, and 77.9% reported having deprivation-related ELA. ELA characterised by threat was associated with edentulism in both male and female participants. Two forms of threat-related ELA exposure were linked to a 1.65-fold and 1.73-fold higher risk for edentulism in both male (95% CI 1.23, 2.21) and female participants (95% CI 1.31, 2.29), compared to no threat-related ELA exposure. Both male (95% CI 2.34, 4.24) and female participants (95% CI 2.49, 4.56) had a 3.15-fold and 3.37-fold higher risk for edentulism when exposed to three or more threat-related ELAs. Conclusion Our findings suggest that ELA marked by threat is linked to an increased risk of edentulism. The biological pathways between different dimensions of ELA and teeth loss should be clarified by future research.